Application of a new Neuromodulation Technology for Control of Human Mentality and Cognitive Strategies - D B Chaivanov; Y A Chudina (Peoples' Friendship University of Russia (RUDN University), 2011)
The article describes the control technology over human cognitive strategies and mentality with the help of the instrumental method of neuromodulation. The implementation and alteration of the cognitive strategy are carried out on the basis of mentality dynamics, defined by its psycho-physiological functions.